Reciprocal Pricing Strategy to Improve MSME Performance - Andriyansah Andriyansah; Fatia Fatimah; Ginta Ginting; Emiliana Sri Pudjiarti (Green Publisher Indonesia, 2024)
This study aims to prove that the new concept of reciprocal pricing can affect the improvement of MSME performance. This study uses a quantitative approach with the sample technique used is Cluster Random Sampling This technique is taken with the argument that this research was conducted in several areas, namely, the tourism area of MSMEs street food vendors, then the building owner sells drinks or other products that are not similar. There were 175 MSMEs that became the object of research using the SEM AMOS analysis tool. Empirical evidence proves that Reciprocal pricing is able to encourage the improvement of MSME performance. Implement a marketing strategy strategy that focuses on building and maintaining marketing relationships between one business unit and another for the long term with the aim of providing different value to customers from competitors. The novelty of this research is Reciprocal Pricing, which is the concept of reciprocal pricing by two or more business units that provide mutual benefits to the agreed price, this variable is thought to improve performance. The implication is that efforts to improve the performance of MSMEs need to use the concept of Reciprocal Pricing in this research which is proven to encourage the improvement of MSME performance. The implementation of reciprocal pricing in improving the performance of MSMEs in tourism areas is proven to increase the number of consumers.